2,2′-Diamino-N,N′-(o-phenylene)dibenzamide - Booysen, Irvin (International Union of Crystallography, 2009)
In the structure of the title compound, C(20)H(18)N(4)O(2), the N—H and C=O bonds are trans to each other and the amide O atoms are syn to the ortho amino N atom in the benzoyl rings. The amide groups form dihedral angles of 8.4 (2) and 13.8 (2)° with their respective benzoyl rings, and dihedral angles of 51.85 (16) and 51.19 (17)° with the phenylenediamine ring. In the crystal, a centrosymmetric dimer is formed by intermolecular N—H⋯O hydrogen bonds, resulting in an R (2) (2)(14) descriptor on a unitary level of graph-set analysis, and three intramolecular N—H⋯O bonds also occur.